Conflict, social capital and managing natural resources: a West African case study - Moore, K. M.; Moore, K. M. (Wallingford :CAB International, 2005)
This book focuses on the Sustainable Agriculture and Natural Resource Management Collaborative Research Support Program (SANREM CRSP) in West Africa, detailing its approach, components and outcomes. It describes the transition of the conflict-ridden agricultural and pastoral systems of arid and semi-arid regions of West Africa to more intensified agricultural and animal husbandry systems. The study investigates technological options and decision tools and explores a replicable methodology for building social capital within a rural community in the Inland Delta of the Niger River. The 17 chapters recount the efforts of researchers and development agents to identify new approaches for sustainable development and the experiences of the local population seeking a pathway from poverty and food insecurity to a healthy economy and environment.
Keywords: CC200 - Extension and Advisory Work; EE110 - Agricultural Economics; EE115 - Natural Resource Economics, (New March 2000); EE125 - Aid, (New March 2000); FF100 - Plant Production; LL180 - Animal Husbandry and Production, (New March 2000); PP000 - Natural Resources (General); UU450 - Community Participation and Development, (New March 2000); UU485 - Social Psychology and Social Anthropology, (New March 2000); UU495 - Conflict, (New March 2000); UU800 - Rural Sociology, (New March 2000); West Africa